Investigation on effects of stochastic loading at the boundary under thermoelasticity with two relaxation parameters - Kant S.; Mukhopadhyay S. (My University, 2025)
The main objective of the present work is to study the responses of stochastic type mechanical distribution at the boundary of an elastic half space in the context of generalized thermoelasticity. In order to compare the results under the stochastic mechanical distribution, we have also considered the case of deterministic mechanical distribution prescribed at the boundary. The stochastic mechanical distribution is considered in such a way that it reduces to a deterministic type distribution as a special case. Laplace transform technique is used to solve the problem and its inversion is carried out by using asymptotic expansions valid for short times to obtain the solution of all the physical field variables like, stress and temperature distributions in the physical domain. Numerical results are found out to compare the effects of stochastic and deterministic load prescribed at the boundary of the elastic half space. © 2017 Elsevier Inc.